DISPERSI SO2 DAN NO2 DARI PEMBANGKIT LISTRIK TENAGA UAP (PLTU) TEMBILAHAN, RIAU - Aryo Sasmita; David Andrio; Risma Nopita (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
The operation of Tembilahan steam power plant produced SO2 and NO2 emissions which can have an impact on the environment and human health. The purpose of this study was to map the distribution patterns of SO2 and NO2 produced from the Tembilahan steam power plant chimney using AERMOD software, comparing the concentrations of SO2 and NO2 gases with ambient air quality standards based on Government Regulation No. 41 of 1999, and comparing the simulation results between the rainy season and the dry season. Modeling is done using 1 year meteorological data with the division of the rainy season and dry season. The modeling results show that the pollutant distribution pattern of Tembilahan steam power plant tends to be towards the southwest. The concentrations of SO2 and NO2 per year were 75.18 µg / m3 and 43.53 µg / m3 respectively which were still below the predetermined quality standards. The dispersion of SO2 and NO2 pollutants in the dry season with a wide range of concentrations is less than during the rainy season.